2011
DOI: 10.1074/jbc.m110.186809
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific Prolyl-4-hydroxylase Domain 2 Knock Out Protects from Acute Myocardial Ischemic Injury

Abstract: Prolylhydroxylase domain proteins (PHD) are cellular oxygen-sensing molecules that regulate the stability of the ␣-subunit of the transcription factor hypoxia inducible factor (HIF)-1. HIF-1 affects cardiac development as well as adaptation of the heart toward increased pressure overload or myocardial infarction. We have disrupted PHD2 in cardiomyocytes (cPhd ؊/؊ ) When oxygen availability is impaired, the resulting hypoxia activates homeostatic mechanisms at the systemic and cellular level (1). Hypoxia-induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 41 publications
(50 reference statements)
4
62
0
2
Order By: Relevance
“…In addition to timing, the duration of PHD inhibition/HIF activation appears to play a critical role in determining disease outcome. Mice with cardiomyocyte-specific Phd2 deletion, for example, had significantly improved cardiac function 3 wk after myocardial IRI (15), whereas sustained Phd2 ablation or tissue-specific HIF-1␣ stabilization resulted in cardiomyopathy (22). While we previously showed that epithelial cell-derived HIF-1 functions as a profibrotic transcription factor in experimental models of CKD (12,13), transient global pre-or postischemic HIF stabilization did not produce adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to timing, the duration of PHD inhibition/HIF activation appears to play a critical role in determining disease outcome. Mice with cardiomyocyte-specific Phd2 deletion, for example, had significantly improved cardiac function 3 wk after myocardial IRI (15), whereas sustained Phd2 ablation or tissue-specific HIF-1␣ stabilization resulted in cardiomyopathy (22). While we previously showed that epithelial cell-derived HIF-1 functions as a profibrotic transcription factor in experimental models of CKD (12,13), transient global pre-or postischemic HIF stabilization did not produce adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…When oxygen availability is limited, PHD enzymatic activity will be inhibited, resulting in stabilization of HIF-1α protein and activation of the HIF-1 pathway (10). Therefore, it is not surprising that pretreatment with prolyl hydroxylase inhibitor or depletion of PHD2, the major prolyl hydroxylator of HIF-α, activates the HIF pathway and elicits HIF-mediated adaptive responses before the onset of hypoxia, attenuating cardiac injury induced by subsequent myocardial ischemia (16)(17)(18)(19). However, it was recently reported that long-term depletion of both PHD2 and PHD3 in the heart resulted in myocardial dysfunction and produced many hallmarks of ischemic cardiomyopathy (23).…”
Section: Discussionmentioning
confidence: 99%
“…Marked induction of HIF-α protein was observed in the region close to the infarct area in a rat model of MI (16). Interestingly, pretreatment with prolyl hydroxylase inhibitor or depletion of PHD2 or PHD3 attenuates myocardial injury induced by myocardial ischemia in several rodent models (16)(17)(18)(19)(20). It was suggested that the HIF pathway plays a central role in this cardioprotective effect (18,21).…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference showed that deletion of HIF PHD1 but not deletion of HIF PHD2 or HIF PHD3 can provide protection against oxidative death of neurons (Siddiq et al, 2009). Conditional deletion of all HIF PHDs has been shown to affect cell viability in response to developmental stimuli in sympathetic neurons (HIF PHD3; Bishop et al, 2008), ischemia in muscle (HIF PHD1; Aragones et al, 2008), and ischemia in the heart (HIF PHD2; Holscher et al, 2011), but these studies while promising, seem to have limited import for posttreatment protection. Future studies using a combination of conditional knockouts and specific pharmacological inhibitors will clarify whether isoform selective HIF PHD inhibition is a viable treatment strategy after stroke.…”
Section: Hypoxia-inducible Factor Prolyl Hydroxylase Inhibition As Anmentioning
confidence: 99%